Development of ELOK (Educational Train Locomotive) Gymnastics in Early Childhood - Ella Nurlaelasari; Wening Nugraheni; Bachtiar Bachtiar (Journal Coaching Education Sports, 2024)
This research focuses on the development of ELOK (Educational Train Locomotive) Gymnastics aimed at early childhood. ELOK Gymnastics is designed to increase children's gross motor activity through a series of fun and structured movements. The development of this exercise follows the ADDIE model which consists of five stages: analysis, planning, development, implementation and evaluation. The research involved an initial survey of 10 HIMPAUDI teachers in Sukabumi District to understand the needs and expectations of early childhood gymnastics. The results showed that ELOK Gymnastics was effective in improving children's motor activity and was well received by teachers and students. The implementation of this exercise is expected to be a positive contribution to early childhood development and provide a reference for future research and development of the exercise.